2019
DOI: 10.1038/s41436-018-0339-3
|View full text |Cite|
|
Sign up to set email alerts
|

The phenotypic spectrum of WWOX-related disorders: 20 additional cases of WOREE syndrome and review of the literature

Abstract: PurposeGermline WWOX pathogenic variants have been associated with disorder of sex differentiation (DSD), spinocerebellar ataxia (SCA), and WWOX-related epileptic encephalopathy (WOREE syndrome). We review clinical and molecular data on WWOX-related disorders, further describing WOREE syndrome and phenotype/genotype correlations.MethodsWe report clinical and molecular findings in 20 additional patients from 18 unrelated families with WOREE syndrome and biallelic pathogenic variants in the WWOX gene. Different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
95
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(109 citation statements)
references
References 37 publications
11
95
3
Order By: Relevance
“…We present the first case of EIMFS (Patient 93) associated with biallelic compound heterozygous variants of WWOX in the context of profound ID, microcephaly, and scoliosis. Reported WWOX encephalopathy cases have had DEEs with infantile spasms and Lennox–Gastaut syndrome; our patient also developed epileptic spasms.…”
Section: Discussionmentioning
confidence: 54%
“…We present the first case of EIMFS (Patient 93) associated with biallelic compound heterozygous variants of WWOX in the context of profound ID, microcephaly, and scoliosis. Reported WWOX encephalopathy cases have had DEEs with infantile spasms and Lennox–Gastaut syndrome; our patient also developed epileptic spasms.…”
Section: Discussionmentioning
confidence: 54%
“…There has been an average of 3 to 4 articles about WOREE every year since 2014. In 2019, Juliette Piard et al reported a series of 20 cases of WOREE (Piard et al, 2019; Table S1). From Table S1, we found that there were more female patients than male ones (boys: girls = 22:38), and the ratio of male to female patients in the Juliette's 20 case series was 8:12.…”
Section: Discussionmentioning
confidence: 99%
“…Since 2014, more than 17 articles have reported the clinical data of WWOX-related epileptic encephalopathy (WOREE ; Table S1; Abdel-Salam et al, 2014;Ben-Salem, Al-Shamsi, John, Ali, & Al-Gazali, 2015;Davids et al, 2019;Ehaideb, Al-Bu Ali, Al-Obaid, Aljassim, & Alfadhel, 2018;Elsaadany, El-Said, Ali, Kamel, & Ben-Omran, 2016;Gribaa et al, 2007;Johannsen et al, 2018;Mallaret et al, 2014;Mignot et al, 2015;Piard et al, 2019;Serin, Simsek, Isik, & Gokben, 2018;Shaukat, Hertecant, El-Hattab, Ali, & Suleiman, 2018;Tabarki et al, 2015;Tarta-Arsene, Barca, Craiu, & Iliescu, 2017;Valduga et al, 2015;Weisz-Hubshman et al, 2019;Yang, Zhang, Song, Yi, & Li, 2019). Here we summarized the clinical features and genetic data of a Chinese infant, and analyzed the characteristics of genotype and clinical phenotype of this kind of disease by reviewing the relevant literatures.…”
Section: Introductionmentioning
confidence: 99%
“…Piard J et al reported the largest cohort of individuals with WOREE syndrome (WWOX‐related epilepticencephalopathy syndrome) which include 20 additional patients from 18 unrelated families. They explained that germline pathogenic variants in WWOX are clearly associated with a severe early‐onset epileptic encephalopathy (Piard and Hawkes, 2019).…”
Section: Discussionmentioning
confidence: 99%